2021
DOI: 10.3389/fimmu.2021.744242
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Secret of SARS-CoV-2 Variants of Concern/Interest and Immune Escape

Abstract: The global pandemic of the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), places a heavy burden on global public health. Four SARS-CoV-2 variants of concern including B.1.1.7, B.1.351, B.1.617.2, and P.1, and two variants of interest including C.37 and B.1.621 have been reported to have potential immune escape, and one or more mutations endow them with worrisome epidemiologic, immunologic, or pathogenic characteristics. This review introduces the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 128 publications
(182 reference statements)
0
38
0
Order By: Relevance
“…Our mathematical model allowed us to evaluate which are the most important characteristics of the variants to become the dominant strain in a partially vaccinated population before the arrival of omicron in the US in early December 2021. Many of the variants of concern/interest have higher transmissibility than the origin variant that emerged from Wuhan, but as we can see this attribute is not sufficient to give rise to a dominant strain [27] . The alpha variant took a long duration to become the dominant strain in early 2021 despite being more transmissible [9] .…”
Section: Discussionmentioning
confidence: 73%
“…Our mathematical model allowed us to evaluate which are the most important characteristics of the variants to become the dominant strain in a partially vaccinated population before the arrival of omicron in the US in early December 2021. Many of the variants of concern/interest have higher transmissibility than the origin variant that emerged from Wuhan, but as we can see this attribute is not sufficient to give rise to a dominant strain [27] . The alpha variant took a long duration to become the dominant strain in early 2021 despite being more transmissible [9] .…”
Section: Discussionmentioning
confidence: 73%
“…Our in vitro experiments revealed that S-217622 exhibits remarkable antiviral potency against all VOCs. Current vaccines and monoclonal antibody medications target the viral spike protein, which accumulates amino acid variations among SARS-CoV-2 variants 16, 17 . In contrast, viral M pro is less divergent, leading to the comparable susceptibility of VOCs to S-217622.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, S-217622 exhibited antiviral activity against all VOCs, while neutralizing antibodies had different reactivities to some VOCs due to mutations in the spike protein (Extended Data Figs. 2a, b) 15, 17 . The remarkable antiviral potency of S-217622 was also reproduced in Vero-TMPRSS2 cells infected with the SARS-CoV-2 Omicron variant (lineage BA.1) (Extended Data Figs.…”
Section: Mainmentioning
confidence: 99%
“…Additionally, the asparagine insertion at residue 146 may impact the viral S1 closed–open conformation, and ACE2 binding [ 58 ]. The Mu variant was also suggested to have a possible immune escape ability, since it was suggested to be strongly resistant to antibodies, and may affect the vaccine efficacy [ 13 , 59 ]. The Mu variant was not considered as a variant of concern, since its characteristics (virulence, resistance to vaccination, immune escape) have not yet been fully researched [ 60 ].…”
Section: Variants Of Interest (Vois) and Former Voismentioning
confidence: 99%